Kinerja Keuangan, Economic Value Added dan Return Saham Dampak Covid-19 - Nurna Aziza; Riska Monalisa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
This study aims to see financial performance through financial statements proxied by financial ratios and Economic Value Added to stock returns due to the impact of Covid-19. This research is expected to prevent investors from making mistakes in investing. The population of this study is non-financial companies listed on the Indonesia Stock Exchange for the 2017-2020 periodThe data collection method used purposive sampling technique, as many as 54 samples with 216 observations that met the research sample criteria. The data were analyzed by using a regression approach.The results showed that the liquidity ratio, profitability ratio, and activity ratio did not affect stock returns, while the solvency ratio and Economic Value Added significantly affected stock returns.